Exploring the lived experiences of those who attended gender-based violence prevention community theatre in Delft - Nqinileyo, Themba (Department of Social Development, 2025)
The year 2023 marks the 29th year since South Africa's first democratic elections in 1994. Close to three decades into democracy, violence persists in our society at an unimaginable scale. This research study explores the lived experiences of those who attended a gender-based violence (GBV) prevention community theatre in Delft. The study presents lived experiences and the meanings attached to those experiences from the perspectives of audience members. Supplementarily, the study explored audience members' definition of GBV and GBV prevention and looks at the contribution of community theatre to GBV prevention. The study used a qualitative approach and a phenomenological design. Data were collected through indepth, face-to-face interviews of 19 participants (ages 18–47 years, mean age = 26) selected from two different recruitment groups; fifteen participants were audience members from the Delft community and four were social service providers in the Delft community working in victim empowerment programs. Data was analysed using interpretive phenomenological analysis (IPA). Data analysis revealed five areas of interest: audience experiences; community theatre as GBV prevention tool; understanding GBV and GBV prevention; challenges faced by victims of GBV; and GBV victim support.